Análisis de la programación de Radio Universitaria 98.5 FM, y su aceptación en la ciudadanía lojana en el periodo mayo-julio 2024 - Troya Alvarado, Alex Francisco (2024)
University radio has established itself as a means of communication that contributes to the production of scientific content in the face of the current news overload. It has influenced the transformation and democratization of information, and has also become an instrument for the formation of critical thinking in students and connects with all members of the university community through the promotion of collective, social and cultural actions. The general objective of this work is to analyze the programming of the radio station at National University of Loja 'UNL radio 98.5 FM' and the acceptance it has among the citizens of Loja. The study used a mixed approach methodology, with a qualitative-quantitative design and a descriptive approach. In addition, the following techniques were applied: interviews with radio experts to learn their criteria, a survey of 398 Lojanos between 18 and 55 years of age, and observation of radio programming. As a result, it was found that the university radio station has several programs, mostly educational and musical, it stands out for the student participation in the construction of the contents, its audience is young with different preferences and its acceptance has a high percentage. It is concluded that the academic nature of the university radio grid allows the involvement of the different careers, promoting the dissemination of academic content and the linkage of the student body with the community. Key words: audience; programming, university radio stations.